PENGARUH METODE BERMAIN JAWABAN TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS X IPS SMA NEGERI 9 PEKANBARU - Irma Novita Desi; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of using Bermain Jawaban learning method toward social students motivation in learning PPKn at SMA Negeri 9 Pekanbaru. This study aims to determine the effect of of using Bermain Jawaban learning method toward students’ motivation in learning PPKn at SMA Negeri 9 Pekanbaru.This research was a quantitative descriptive study that was experimental.Population in this study were social students of class X IPS SMA Negeri 9 Pekanbaru. The sample in this research was taken based on